2001
DOI: 10.1021/jf0111099
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS Analysis of Hydrophobic Root Exudates of Sorghum and Implications on the Parasitic Plant Striga asiatica

Abstract: Striga asiatica is a parasitic angiosperm that responds to germination stimulants produced by host plants, including many grasses. GC-MS analyses of hydrophobic root exudates of sorghum revealed the root exudates to be composed of fatty acids, resorcinol, and a series of structurally related hydroquinones, three of which were previously unknown. High yields of resorcinol and the hydroquinone series were detected in sorghum. At least one of the hydroquinones induces germination in Striga, and the resorcinol is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 18 publications
3
26
0
Order By: Relevance
“…Although very little variation in the levels of dihydrosorgoleone (measured as sorgoleone) was found between many of the high and low germination stimulant accessions (N13, P954063, SRN39, Framida and IS9830) used by study, others reported a nearly 30-fold variation among 25 sorghum varieties (Nimbal et al 1996). Some have also suggested that variations in the levels of resorcinol (methoxy-dihydrosorgoleone), a biochemically related metabolite, could stabilize dihydrosorgoleone, preserving its function and thereby modulating the Striga germination stimulant activity in the rhizosphere (Erickson et al 2001). Alkylresorcinol synthase 1 (ARS1), a sorghum gene involved in biosynthesis of dihydrosorgoleone, was recently identified on SBI-05 and cloned (Cook et al 2010; Phytozome database sorghum gene ID is Sb05g022500).…”
Section: Discussionmentioning
confidence: 99%
“…Although very little variation in the levels of dihydrosorgoleone (measured as sorgoleone) was found between many of the high and low germination stimulant accessions (N13, P954063, SRN39, Framida and IS9830) used by study, others reported a nearly 30-fold variation among 25 sorghum varieties (Nimbal et al 1996). Some have also suggested that variations in the levels of resorcinol (methoxy-dihydrosorgoleone), a biochemically related metabolite, could stabilize dihydrosorgoleone, preserving its function and thereby modulating the Striga germination stimulant activity in the rhizosphere (Erickson et al 2001). Alkylresorcinol synthase 1 (ARS1), a sorghum gene involved in biosynthesis of dihydrosorgoleone, was recently identified on SBI-05 and cloned (Cook et al 2010; Phytozome database sorghum gene ID is Sb05g022500).…”
Section: Discussionmentioning
confidence: 99%
“…The term sorgoleone is most frequently used to describe the compound corresponding to the predominant congener identified in sorghum root exudates (Netzly et al, 1988;Kagan et al, 2003), 2-hydroxy-5-methoxy-3-[(Z,Z)-8',11',14'-pentadecatriene]-p-benzoquinone (Figure 1), which has been estimated to account for between ;40 and 90% of the exudate material (w/w) in various accessions (e.g., Nimbal et al, 1996;Czarnota et al, 2001;Baerson et al, 2008a;Dayan et al, 2009). The remaining exudate consists primarily of 4,6-dimethoxy-2-[(Z,Z)-8',11',14'-pentadecatriene]resorcinol (methoxy-dihydrosorgoleone) and sorgoleone congeners differing in the length or degree of saturation of the aliphatic side chain and in the substitution pattern of the quinone ring (Erickson et al, 2001;Kagan et al, 2003;Rimando et al, 2003;Dayan et al, 2009). The fact that sorgoleone acts as a potent broad-spectrum inhibitor active against many agronomically important monocotyledonous and dicotyledonous weed species and appears to affect multiple targets in vivo (e.g., Netzly and Butler, 1986;Einhellig and Souza, 1992;Nimbal et al, 1996;Rimando et al, 1998;Czarnota et al, 2001;Bertin et al, 2003;Duke, 2003) may make it promising for development as a natural product alternative to synthetic herbicides (Duke, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The root hairs of sorghum produce an oily exudate containing the lipid benzoquinone sorgoleone (2-hydroxy-5-methoxy-3-[(8′Z, 11′Z)-8′, 11′, 14′-pentadecatriene]-p-benzoquinone), which is a potent allelochemical (Netzly and Butler, 1986;Inderjit and Duke, 2003). Sorgoleone and its 1 4-hydroquinone form together account for~50% of the oily exudates from sorghum root hairs (Erickson et al, 2001;Dayan et al, 2009). The remaining percentage consists primarily of alkyl resorcinol analogs, along with small amounts of several sorgoleone congeners that vary in the substitutions in the aromatic ring (Fate and Lynn, 1996;Rimando et al, 1998;Kagan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%